Publishing entrepreneurship research: Strategies for success distilled from a review of over 3, 500 submissions. (2nd January 2021) - Liguori, Eric W.; El Tarabishy, Ayman; Passerini, Katia
ABSTRACT: This editorial provides an overview of the inner workings of the Journal of Small Business Management and its editorial and peer review processes. In doing so it offers practical insights relevant to authors looking to publish scholarly work in the fields of entrepreneurship and small business scholarship. Specifically, this article discusses the process JSBM uses to review all submissions, the most common causes for a desk reject decision, guidance on best practices for manuscript submission and publication success, and the importance of engagement with the scholarly community.